Method for enhancing zero-valent iron crushing in wet grinding
By using sodium sulfide aqueous solution to vulcanize and grind zero-valent iron in a wet ball mill, the problem of zero-valent iron crushing is solved, and the efficient crushing of zero-valent iron to the nanoscale is achieved, improving its performance in environmental restoration and industrial applications.
Patent Information
- Application Number
- CN202411614452.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to effectively crush zero-valent iron to the nanoscale, and the oxidation and particle size of iron during the crushing process are difficult to control, affecting its performance in environmental restoration and industrial applications.
The sodium sulfide aqueous solution is used to vulcanize and modify the zero-valent iron, and grind it with zirconia beads in a wet ball mill to control the grinding temperature and time, and efficient crushing of zero-valent iron is achieved through the formation of the iron sulfide layer and the mechanical force.
Effectively preventing iron oxidation and promoting the crushing of zero-valent iron, it can crush zero-valent iron to the nanoscale, improve its specific surface area and reactivity, and enhance its performance in environmental restoration and industrial applications.
Smart Images

Figure CN119588941A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of particle refinement, and in particular to a method for enhancing the pulverization of zero-valent iron in wet grinding. Background Art
[0002] In the past two decades, the application of ultrafine zero-valent iron (ZVI), such as micron- or nano-ZVI, in contaminated site remediation and industrial wastewater treatment has attracted widespread attention. In these applications, the size of ZVI particles is a key factor in determining their performance and applicability. Compared with bulky ZVI particles, smaller ZVI particles generally have higher specific surface area and reactivity. These smaller particles also have better fluid dynamics: they can overcome gravity through fluid turbulence or electrostatic repulsion generated by the electrolyte coating on the particle surface, making them more easily suspended in water or transported by water flow. The increasing application of ultrafine ZVI particles in the environmental field requires corresponding large-scale production technology.
[0003] Mechanical grinding is an environmentally friendly method of particle refinement. During the grinding process, grinding balls (beads) collide and squeeze the solid particles trapped between them through mechanical agitation, causing the particles to break and eventually be crushed. Grinding machines of various types and sizes have been commercialized, and crushing technology has been widely used in industrial fields such as pigments, inks and cosmetics. Grinding technology has also been used in the production of ultrafine zero-valent iron in the environmental field, where grinding has been shown to be able to crush zero-valent iron particles to the nanometer scale.
[0004] A key issue in the pulverization of zero-valent iron by grinding is that the main component of zero-valent iron, metallic iron (Fe(0)), is ductile and can withstand severe plastic deformation. Therefore, although zero-valent iron is relatively easy to be plastically deformed into flakes, further breaking these formed zero-valent iron flakes is not as easy as the initial deformation. Therefore, repeated grinding and large energy input are required to accumulate metal dislocations and defects, induce crack formation in the flake structure, and then flake breakage occurs.
[0005] To date, the pulverization of ductile metals by ball milling has not yet achieved optimal results. Existing research on zero-valent iron (ZVI) grinding has mainly focused on compounding ZVI with other materials (such as carbon, FeSx or nickel) to prepare composite materials, rather than focusing on the pulverization of ductile ZVI. In previous studies using water as the grinding medium, although attempts were made to prepare nano-ZVI by grinding micron-sized ZVI, the effective iron content of the resulting nanoparticles was usually less than 50%, with most of the metallic iron oxidized due to the mechanochemical effect that accelerated the reaction between iron and water. As the iron is oxidized to iron oxides, the material loses its inherent reducing ability and thus loses its application value. In the field of materials science, this pulverization problem is often overlooked, and grinding is more used in the production of metal alloys. In the alloy preparation process, particle pulverization is usually regarded as a disadvantage and should be avoided as much as possible.
[0006] CN118595433A discloses a method for preparing sulfur-nitrogen modified zero-valent iron by wet ball milling, sulfur-nitrogen modified zero-valent iron and its application, wherein zero-valent iron, nitrogen-sulfur ligands and alcohol solvents are mixed into a slurry and then ball milled. The sulfur-nitrogen modification process of this patent usually needs to be carried out under harsh conditions such as high temperature and high pressure, which increases production costs and limits the operability of the process and the feasibility of industrial application. At the same time, although this patent improves the performance of zero-valent iron (zero-valent iron), it does not solve its crushing problem.
[0007] CN 113102761 B discloses a method for preparing a composite zero-valent iron material based on wet ball milling of soluble sulfides. A soluble sulfide aqueous solution is used as a wet ball milling solvent, and a composite zero-valent iron material is obtained after wet ball milling using a ball milling medium. This method has a small degree of crushing of zero-valent iron in practical applications. Since the ductility problem of iron is not effectively solved, the particle size of the ground zero-valent iron is still large and it is difficult to achieve nano-level ultrafine particles, which limits its application in fields requiring high reactivity. In addition, this method can only improve the surface properties of zero-valent iron to a certain extent by simply ball milling elemental sulfur powder and iron, but fails to significantly improve the overall reactivity and stability of zero-valent iron. Therefore, the application effect of this technology in dealing with complex polluted environments is also very limited.
[0008] CN 116275059 A discloses a method for preparing sulfide nano zero-valent iron material based on elemental sulfur wet ball milling and its application. The method adopts wet ball milling of iron powder to be processed and elemental sulfur powder using ball milling medium to prepare composite sulfide zero-valent iron. The patent does not involve how to achieve efficient crushing of zero-valent iron by ball milling, and cannot meet the actual application requirements of ultrafine zero-valent iron particles. Although the use of sodium sulfide helps to protect the iron content, the patent does not systematically optimize the grinding conditions, time and auxiliary agent concentration, and thus cannot achieve the best crushing effect and material performance.
[0009] In summary, how to crush zero-valent iron into smaller particle size while maintaining its high effective iron content remains a major challenge. Summary of the invention
[0010] The present invention is made to solve the above-mentioned problem, and aims to provide a method for enhancing the crushing of zero-valent iron in wet grinding, so that the zero-valent iron can be crushed to a smaller particle size while maintaining the iron content.
[0011] The present invention provides a method for enhancing the crushing of zero-valent iron in wet grinding, which has the following characteristics. The crushing steps are specifically as follows: S1, adding zero-valent iron powder to a sodium sulfide aqueous solution to form a slurry to be ground; S2, loading grinding beads in a wet ball mill, adding the slurry to be ground into the wet ball mill for grinding to obtain a slurry, the grinding temperature is 8-12°C, and the grinding time is 10-640min; S3, taking out the slurry from the wet ball mill, placing the slurry into a magnetic separation device for solid-liquid separation, collecting the ground sulfide-modified zero-valent iron particles and washing them with ethanol; and S4, placing the washed sulfide-modified zero-valent iron particles in a vacuum drying oven, controlling the temperature to be dried at 40-60°C until the residual moisture and ethanol are completely removed.
[0012] The method for enhancing the crushing of zero-valent iron in wet grinding provided by the present invention may also have the following characteristics: the content of zero-valent iron in the zero-valent iron powder is higher than 98.5%, and the median particle size of the zero-valent iron particles is 3.0-3.2 microns.
[0013] The method for enhancing the pulverization of zero-valent iron in wet grinding provided by the present invention may also have the following characteristics: wherein the concentration of the sodium sulfide aqueous solution is 28-29 g / L.
[0014] In the method for enhancing the pulverization of zero-valent iron in wet grinding provided by the present invention, it can also have the following characteristics: wherein the grinding beads are zirconia beads with a weight of 0.75 kg and a diameter of 0.3 mm.
[0015] The method for enhancing the pulverization of zero-valent iron in wet grinding provided by the present invention may also have the following characteristics: during the grinding process, the temperature in the cavity of the wet grinder is controlled at 8-12°C.
[0016] The method for enhancing the pulverization of zero-valent iron in wet grinding provided by the present invention may also have the following feature: wherein the rotation speed of the wet ball mill is 1900-2100 rpm.
[0017] The method for enhancing the pulverization of zero-valent iron in wet grinding provided by the present invention may also have the following characteristics: wherein the grinding time is 100-640 minutes.
[0018] Functions and Effects of the Invention According to the method for enhancing the crushing of zero-valent iron in wet grinding involved in the present invention, the present invention uses sodium sulfide solution to sulfide-modify zero-valent iron, and the sulfide ions react with the surface of zero-valent iron to form an iron sulfide layer. The iron sulfide has non-ductile characteristics, which can effectively inhibit the cold welding effect between zero-valent iron particles and prevent the particles from aggregating into large particles again during the grinding process; the iron sulfide particles will be embedded in the flaky structure of zero-valent iron like a wedge under the action of mechanical force, further promoting the fracture of the flaky iron particles and forming smaller iron particles; as the grinding time increases, the iron sulfide particles are gradually refined to the nanometer level, and they can fill the gaps between the grinding beads and the zero-valent iron particles, increasing the contact probability between the particles and further improving the crushing efficiency. Therefore, the method for enhancing the crushing of zero-valent iron in wet grinding of the present invention has the effect of effectively preventing the oxidation of iron and promoting the crushing of zero-valent iron. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic diagram of the process of preparing ultra-zero-valent iron by wet ball milling.
[0020] Figure 2 It is a schematic diagram of the wet ball milling method using water as the grinding agent.
[0021] Figure 3 This is a schematic diagram of the wet ball milling method using alcohol as the grinding agent.
[0022] Figure 4 It is a process flow chart of the method for pulverizing zero-valent iron in enhanced wet grinding of the present invention.
[0023] Figure 5 It is a structural schematic diagram of the wet ball mill of the present invention.
[0024] Figure 6 These are views of the sulfided zero-valent iron after ball milling for 10 minutes, 40 minutes, and 640 minutes in Example 1 of the present invention under a scanning electron microscope.
[0025] Figure 7 These are views obtained through a scanning electron microscope after ball milling of zero-valent iron in alcohol for 10 minutes, 40 minutes, and 640 minutes in Comparative Example 1 of the present invention.
[0026] Figure 8 It is a comparison chart of the average particle sizes of the zero-valent iron in Example 1 of the present invention and Comparative Example 1 measured in a zeta potential meter at 0 minutes, 40 minutes, 80 minutes, 160 minutes, 320 minutes and 640 minutes of ball milling.
[0027] Fig. 9 These are the SEM images of the zero-valent iron in Example 1 and Comparative Example 1 of the present invention and the statistical results of IMAGE PRO.
[0028] Fig.10 It is a graph showing the change in specific surface area of zero-valent iron in Example 1 of the present invention and Comparative Example 1 when ball-milled in a sodium sulfide solution and in alcohol.
[0029] Fig.11 1 is the removal curve of Cr(VI) by Example 1 of the present invention, Comparative Example 1 and the original iron powder.
[0030] Fig.12 It is the transmission performance of Example 1 and Comparative Example 1 of the present invention and the original iron powder in the porous medium.
[0031] Fig.13 It is a schematic diagram of the ball milling time and average particle size of Example 1 of the present invention and Comparative Examples 2-5. DETAILED DESCRIPTION
[0032] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the following embodiments and the accompanying drawings specifically illustrate the method for crushing zero-valent iron in enhanced wet grinding of the present invention.
[0033] Figure 1 This is a schematic diagram of the process of preparing ultra-zero-valent iron by wet ball milling. Figure 2 It is a schematic diagram of the wet ball milling method using water as the grinding agent. Figure 3 This is a schematic diagram of the wet ball milling method using alcohol as the grinding agent. Figure 4 It is a process flow chart of the method for pulverizing zero-valent iron in enhanced wet grinding of the present invention.
[0034] like Figure 1-4 As shown, the method for enhancing the crushing of zero-valent iron in wet grinding in this embodiment specifically includes the following steps: S1, adding zero-valent iron powder to the sodium sulfide aqueous solution to form a slurry to be ground.
[0035] S2, loading zirconium oxide beads as grinding beads into a wet ball mill, adding the slurry to be ground into the wet ball mill for grinding to obtain slurry.
[0036] S3, taking out the slurry from the wet ball mill, placing the slurry into a magnetic separation device for solid-liquid separation, collecting the ground sulfide-modified zero-valent iron particles and washing them with ethanol.
[0037] S4, placing the washed sulfurized modified zero-valent iron particles in a vacuum drying oven for drying until the residual water and ethanol are completely removed.
[0038] Figure 5 Schematic diagram of the structure of the wet ball mill 100 of the present invention.
[0039] like Figure 5 As shown, the wet ball mill used in the above method of the present invention comprises a reactor housing 10, a rotor 20, an end cover 31 and a driving mechanism 40. The driving mechanism 40 is used to drive the rotor 20 to rotate, and comprises a main shaft 42, a bearing seat 41 and a pulley 45.
[0040] The reactor shell 10 is generally cylindrical, and has a cavity formed inside, which is the reaction chamber 11. The reactor shell 10 is provided with a feed port 12 and a discharge port 13 connected to the reaction chamber 11, which are used to allow the slurry to enter and flow out of the reaction chamber 11, respectively.
[0041] In the reactor shell 10, a cooling water chamber 14 is formed around the reaction chamber 11 and is not connected to the reaction chamber 11, and is used to contain cooling water for cooling the reaction chamber 11. The cooling water can enter the cooling water chamber through the cooling water inlet 15 and flow out of the cooling water chamber from the cooling water outlet 16.
[0042] The rotor 20 is disposed in the reaction chamber 11 and is columnar with a plurality of annular sheets disposed on the circumference. The surface of the rotor is covered with a layer of polyurethane material to reduce the wear of the ball milling beads and the like on the rotor body.
[0043] The end cover 30 is disposed at one end of the reactor housing 10 , and a middle end cover 31 is installed on the end of the end cover 30 away from the reactor housing 10 .
[0044] The bearing seat 41 is disposed on the other side of the middle end cover 31 relative to the end cover 30 .
[0045] The main shaft 42 is installed in the bearing seat 41 through the bearing 43, and one end of the main shaft 42 passes through the middle end cover 31 and the end cover 30 in sequence and extends into the reaction chamber 11. This end is connected to the rotor 20, so that the main shaft 42 can drive the rotor 20 to rotate.
[0046] A mechanical seal assembly 44 is also provided in the end cover 30 . The mechanical seal assembly 44 is sleeved on the main shaft 42 and is located close to the reaction chamber 11 . The mechanical seal assembly 44 is used to form a seal on the main shaft 42 to prevent the liquid in the reaction chamber 11 from leaking to the bearing seat 41 and other parts.
[0047] The other end of the main shaft 42 extends to the outside of the bearing seat 41, and is fixed by a locking nut 46 and a bearing cover plate 47, and a main pulley 45 is fixed on this end. The driving motor 40 drives the main pulley 45 to rotate through a belt transmission mechanism, so that the main shaft 42 rotates and drives the rotor 20 to rotate in the reaction chamber 11. When there is slurry containing ball milling beads in the reaction chamber 11, the high-speed rotation of the rotor 20 can strongly stir the slurry, so that the slurry can undergo a mechanochemical reaction under the action of the ball milling beads; a large amount of heat will be generated in the process, and the heat can be taken away by cooling water.
[0048] Example 1 S1, add zero-valent iron powder to a sodium sulfide aqueous solution with a concentration of 28.6 g / L, stir well to form a slurry to be ground, the content of zero-valent iron in the zero-valent iron powder is 98.8%, and the median particle size of the zero-valent iron particles is 3.1 microns.
[0049] S2, loading zirconia beads with a weight of 0.75 kg and a diameter of 0.3 mm as grinding beads in a wet ball mill, adding the slurry to be ground into the wet ball mill for grinding to obtain slurry, the grinding temperature is 10°C, and the rotation speed of the wet ball mill is 2000 rpm.
[0050] S3, taking out slurry samples when the grinding time reaches 40min, 80min, 100min, 160min, 320min and 640min respectively, placing each slurry sample in a magnetic separation device for solid-liquid separation, collecting the ground sulfide-modified zero-valent iron particles respectively and washing them with ethanol until the residual sodium sulfide solution and other impurities are removed.
[0051] S4, placing the washed sulfurized modified zero-valent iron particles in a vacuum drying oven respectively, controlling the temperature at 50° C. for drying until the residual water and ethanol are completely removed.
[0052] Figure 6 3 and 4 are views of a scanning electron microscope after ball milling of zero-valent iron sulfide for 10 minutes, 40 minutes and 640 minutes in an example of the present invention.
[0053] like Figure 6 As shown, in the initial 10 min of grinding, the zero-valent iron particles only underwent initial plastic deformation.
[0054] As the grinding time was extended to 40 min, the zero-valent iron particles further transformed into a flaky structure with a particle size of more than 4 μm, and the size of some particles had dropped to about 4.03 μm.
[0055] After a long grinding period (640 min), the zero-valent iron particles underwent significant pulverization, forming flake-like particles with a size of approximately 0.74 μm to 5.22 μm. The image shows the details of the FeSx particles embedded in the zero-valent iron flake structure, indicating that the FeSx particles played a role in enhancing pulverization at this stage.
[0056] The picture also magnifies the details of the zero-valent iron particles after 640 minutes of ball milling, and it can be seen that the particle size is further reduced to 0.41 microns. This shows that after a long period of ball milling, the zero-valent iron particles have been successfully crushed to the nanometer level, showing a good crushing effect.
[0057] Comparative Example 1 S1, adding zero-valent iron powder to alcohol, stirring thoroughly to form a slurry to be ground, the content of zero-valent iron in the zero-valent iron powder is 98.8%, and the median particle size of the zero-valent iron particles is 3.1 microns.
[0058] S2, loading zirconia beads with a weight of 0.75 kg and a diameter of 0.3 mm as grinding beads in a wet ball mill, adding the slurry to be ground into the wet ball mill for grinding to obtain slurry, the grinding temperature is 10°C, and the rotation speed of the wet ball mill is 2000 rpm.
[0059] S3, taking out slurry samples when the grinding time reaches 40 min, 80 min, 100 min, 160 min, 320 min and 640 min respectively, placing the slurry into magnetic separation equipment for solid-liquid separation, and collecting the ground zero-valent iron particles respectively.
[0060] S4, placing the washed zero-valent iron particles in a vacuum drying oven respectively, controlling the temperature at 50° C. for drying until the residual ethanol is completely removed.
[0061] Figure 7 These are views obtained through a scanning electron microscope after ball milling of zero-valent iron in alcohol for 10 minutes, 40 minutes, and 640 minutes in Comparative Example 1 of the present invention.
[0062] like Figure 7 As shown in the figure, after 10 minutes of grinding, the zero-valent iron particles underwent initial plastic deformation, but the overall morphology of the particles did not change much and remained relatively large. The measurement showed that the size of the particles was about 2.73 microns to 4.22 microns, the surface was relatively rough, and the particle morphology still appeared to be large, loose blocks.
[0063] After 40 minutes of grinding, the shape of the zero-valent iron particles gradually changed into flakes, and the size increased slightly to 4.70 microns and 4.13 microns. This shows that during the long ball milling process, the zero-valent iron particles are prone to cold welding, and the particles re-aggregate into larger flake structures, resulting in unsatisfactory crushing effects.
[0064] After 640 minutes of long grinding, the average particle size of the particles ranged from 3.03 microns to 2.96 microns, showing further development of the flaky structure. However, the particle size was still large, and the morphology tended to be flaky, thin and wide, indicating that the pulverization efficiency of zero-valent iron was low and it could not be effectively pulverized to a smaller particle size by mechanical force alone.
[0065] The enlarged image shows that after 640 minutes of grinding, the size of some zero-valent iron particles is 2.34 microns to 2.52 microns. These particles still have a flaky structure and a relatively smooth surface. There is still a certain cold welding phenomenon between the particles, and a significant nano-scale crushing effect cannot be achieved.
[0066] Figure 8 It is a comparison chart of the average particle sizes of the zero-valent iron in Example 1 of the present invention and Comparative Example 1 measured in a zeta potential meter at 0 minutes, 40 minutes, 80 minutes, 160 minutes, 320 minutes and 640 minutes of ball milling.
[0067] like Figure 8 As shown in the figure, before the ball milling started, the average particle size of the zero-valent iron particles in the two solvents was the same, about 3000 nanometers (i.e., 3 microns), which means that the initial zero-valent iron particles had the same morphology and particle size and had not undergone any crushing treatment.
[0068] After 40 minutes of ball milling, the average particle size of zero-valent iron particles in both solvents decreased. However, it is obvious that the particle size of zero-valent iron in sodium sulfide solution decreased more significantly, from 3000 nanometers to about 2500 nanometers, while the particle size of zero-valent iron in alcohol only decreased to about 4000 nanometers.
[0069] This indicates that under the same grinding time, the crushing effect of zero-valent iron in sodium sulfide solution is significantly better than that in alcohol, which may be due to the inhibitory effect of sodium sulfide on the cold welding effect and its wedging effect, which better promotes particle crushing.
[0070] After 80 minutes of ball milling, the average particle size of the zero-valent iron particles in the sodium sulfide solution continued to decrease to about 2000 nanometers, while the particle size of the zero-valent iron particles in the alcohol remained at about 3500 nanometers. At this time, the pulverization effect in the sodium sulfide solution was more significant.
[0071] After 160 minutes of ball milling, the particle size of the zero-valent iron particles in the sodium sulfide solution further decreased to about 1500 nanometers, while the zero-valent iron particles in the alcohol still stagnated at around 3000 nanometers.
[0072] During this period, the sodium sulfide solution significantly improved the crushing efficiency of the zero-valent iron particles, and the particle size continued to decrease.
[0073] After 320 minutes of ball milling, the particle size of zero-valent iron particles in the sodium sulfide solution further decreased to nearly 1000 nanometers, while the zero-valent iron particles in the alcohol were still larger than 2500 nanometers. This once again verifies the enhanced effect of sodium sulfide solution on the crushing of zero-valent iron.
[0074] After 640 minutes of ball milling, the average particle size of the zero-valent iron particles in the sodium sulfide solution further decreased to below about 800 nanometers, while the zero-valent iron particles in the alcohol remained at a level of about 2000 nanometers.
[0075] The final results show that after a long period of ball milling, sodium sulfide solution can effectively crush zero-valent iron particles to the nanometer level, while in alcohol, due to the influence of the cold welding effect, the particle size reduction is limited.
[0076] Fig. 9 These are the SEM images of the zero-valent iron in Example 1 and Comparative Example 1 of the present invention and the statistical results of IMAGE PRO.
[0077] like Fig. 9 As shown in the figure, the particle size distribution of zero-valent iron particles after ball milling in alcohol for 640 minutes shows the particle size distribution of zero-valent iron particles after ball milling in alcohol for 640 minutes. The largest particles are distributed in the range of 2.0-3.0 microns (accounting for 26.3%) and 3.0-4.0 microns (accounting for 23.5%), and the overall particle size is relatively large. The proportion of particles with smaller particle sizes (such as 0.0-1.0 microns) is relatively low (only 1.2%), which shows that alcohol as a solvent has not effectively promoted the pulverization of zero-valent iron, and a large number of large particles are still present.
[0078] The particle size distribution after ball milling in sodium sulfide shows the particle size distribution of zero-valent iron particles after ball milling in sodium sulfide solution for 640 minutes. Compared with alcohol, the particle size distribution of particles in sodium sulfide solution is significantly smaller, and most of the particles are concentrated in the range of 0.0-1.0 microns (60.5%) and 1.0-2.0 microns (28.3%). This shows that the sodium sulfide solution effectively promotes the refinement of zero-valent iron particles during the ball milling process, significantly reducing their particle size and achieving a nano-level crushing effect.
[0079] Fig.10 It is a graph showing the change in specific surface area of zero-valent iron in Example 1 of the present invention and Comparative Example 1 when ball-milled in a sodium sulfide solution and in alcohol.
[0080] like Fig.10 Figure 2 shows the initial stage (0 minutes): Before the ball milling begins, the surface area of the zero-valent iron particles in both solvents is about 0.4 m² / g. This is the initial surface area of the zero-valent iron powder without any milling treatment.
[0081] Ball milling for 100 minutes: As the ball milling time increases, the specific surface area of zero-valent iron particles increases rapidly. Especially in the sodium sulfide solution, the specific surface area of zero-valent iron rises rapidly to about 20 m² / g in the first 100 minutes, showing a significant crushing effect. In contrast, the specific surface area of zero-valent iron in alcohol increases more slowly, reaching only about 12 m² / g. This shows that sodium sulfide can effectively promote the crushing of zero-valent iron particles and increase their specific surface area in the early ball milling stage.
[0082] Ball milling for 100 to 640 minutes: After the ball milling time reaches 100 minutes, the specific surface area of zero-valent iron in the sodium sulfide solution tends to be stable, maintaining between 20-22 m² / g, indicating that the particles have been effectively crushed to a smaller stable size, and further ball milling failed to significantly increase the specific surface area.
[0083] On the other hand, the specific surface area of zero-valent iron in alcohol slowly increased after 100 minutes and finally stabilized at about 15 m² / g at 640 minutes. This shows that although alcohol can also increase the specific surface area of zero-valent iron under longer grinding time, its pulverization efficiency and effect are far inferior to that of sodium sulfide.
[0084] Specific surface area is an important indicator that measures the ratio of a material's exposed surface to its total mass. Generally, the larger the specific surface area, the more reactive the material. In environmental remediation applications, the specific surface area of zero-valent iron is directly related to its ability to treat pollutants.
[0085] Sodium sulfide solution can more effectively increase the specific surface area of zero-valent iron during the ball milling process, which means that the zero-valent iron particles prepared by it will have stronger reactivity and higher environmental treatment efficiency.
[0086] Fig.11 1 is the removal curve of Cr(VI) by Example 1 of the present invention, Comparative Example 1 and the original iron powder.
[0087] like Fig.11 As shown, original iron powder: The blue curve represents the effect of using original iron powder to treat Cr(VI). In the early stage of the reaction, the concentration of Cr(VI) slowly decreased from 10 mg / L until 120 minutes later, when the concentration of Cr(VI) was still about 6 mg / L. This shows that the iron powder that has not been ball-milled has a slow removal effect on Cr(VI) and a low reaction rate. The original iron powder cannot quickly and effectively reduce Cr(VI) due to its large particles, small specific surface area, and low reaction activity.
[0088] Iron powder ball-milled in alcohol: The pink curve represents the effect of iron powder ball-milled in alcohol on Cr(VI). Compared with the original iron powder, the iron powder ball-milled in alcohol has an improved removal effect on Cr(VI) within the first 40 minutes, but the concentration of Cr(VI) still decreases slowly. By 120 minutes, the concentration of Cr(VI) dropped to about 4 mg / L. This shows that the ball milling treatment does enhance the reactivity of the iron powder, but because the iron powder particles ball-milled in alcohol are still large and the cold welding effect is obvious, the increase in specific surface area is limited, and the efficiency of removing Cr(VI) is still not ideal.
[0089] Iron powder ball-milled in sodium sulfide: The red curve represents the effect of iron powder ball-milled in sodium sulfide solution on Cr(VI). It can be seen that this treatment method quickly reduced the concentration of Cr(VI) from an initial 10 mg / L to nearly 0 mg / L within the first 20 minutes. This shows that the iron powder ball-milled in sodium sulfide is extremely reactive and can quickly reduce and remove Cr(VI).
[0090] At 120 minutes, the concentration of Cr(VI) dropped to almost 0, showing an extremely excellent removal effect. The iron powder ball-milled in sodium sulfide can react with Cr(VI) more effectively due to its larger specific surface area and higher reactivity, and the presence of sodium sulfide may further promote the reduction process of Cr(VI).
[0091] Fig.12 It is the transmission performance of Example 1 and Comparative Example 1 of the present invention and the original iron powder in the porous medium.
[0092] like Fig.12 As shown, including a schematic diagram of the experimental apparatus, the figure shows a typical sand column experimental apparatus for studying the transport performance of zero-valent iron particles in porous media. The length of the sand column is 30 cm and the diameter is 2 cm.
[0093] A peristaltic pump was used to pump the suspension containing zero-valent iron into the column from the bottom at a flow rate of 10 mL / min. The liquid flowed through the sand layer and flowed out from the top.
[0094] Agitation and mixing: The suspension was kept uniformly dispersed in the flask by mechanical stirring (200 rpm) before entering the sand column to ensure uniform distribution of the zero-valent iron particles in the fluid.
[0095] The transmission performance of zero-valent iron in the sand column: Original iron powder: The left column is filled with a suspension of original zero-valent iron (without any ball milling treatment). The experiment shows that the original zero-valent iron has the worst transmission performance. After 5 minutes, the black zero-valent iron particles are almost completely retained at the bottom of the column, and the transmission height is only 14.8 cm. The particle size is large (3083 nanometers), which makes it difficult to migrate effectively in the sand column, indicating that its transmission ability in porous media is weak.
[0096] Iron powder ball-milled in alcohol for 640 minutes: The middle column is filled with zero-valent iron that has been ball-milled for 640 minutes and treated in alcohol. Compared with the original iron powder, the zero-valent iron ball-milled in alcohol shows a certain degree of transport improvement, and the transport height increases to 26.8 cm after 5 minutes of the experiment. However, its transport performance is still not ideal, mainly because its particle size is still large (3342 nanometers), which hinders effective diffusion in the sand layer.
[0097] Iron powder ball-milled in sodium sulfide for 640 minutes: The column on the right is filled with zero-valent iron after ball-milling in sodium sulfide solution for 640 minutes. The zero-valent iron under this treatment condition shows significantly better transport properties, almost filling the entire sand column (the transport height is close to 30 cm). In addition, the particle size is significantly reduced to 874 nanometers, making it easier to diffuse and transport in the sand layer.
[0098] Comparison of transport performance: The experimental results clearly show that the transport performance of zero-valent iron is closely related to its particle size. The smaller the particle size, the better the transport effect of zero-valent iron in porous media. The original iron powder is almost impossible to transport in the sand column due to its large particle size; the zero-valent iron ball-milled in alcohol has some improvement, but it is still not ideal; while the zero-valent iron ball-milled in sodium sulfide solution has the best transport performance due to the significantly reduced particle size.
[0099] The role of sodium sulfide: Sodium sulfide, as a ball milling aid, not only significantly improves the crushing effect of zero-valent iron (reduces particle size), but also improves its transmission capacity in porous media. This is of great significance for practical applications, especially in environmental remediation projects that require particles to migrate in groundwater or soil. The use of this modified zero-valent iron can greatly improve the remediation efficiency.
[0100] Environmental remediation application potential: Zero-valent iron ball-milled in sodium sulfide is more suitable for environmental remediation, such as groundwater pollution control, due to its better transport performance and reactivity. Good transport capacity in porous media means that this zero-valent iron can reach the pollution source more effectively for deep remediation.
[0101] Comparative Example 2 On the basis of the experimental steps of Example 1, the sodium sulfide aqueous solution with a concentration of 28.6 g / L was replaced with a sodium thiosulfate aqueous solution with a concentration of 28.97 g / L.
[0102] Comparative Example 3 On the basis of the experimental steps of Example 1, the sodium sulfide aqueous solution with a concentration of 28.6 g / L was replaced with a sodium thiosulfate aqueous solution with a concentration of 28.97 g / L.
[0103] Comparative Example 4 On the basis of the experimental steps of Example 1, the sodium sulfide aqueous solution with a concentration of 28.6 g / L was replaced by a thiourea ethanol solution with a concentration of 27.89 g / L.
[0104] Comparative Example 5 On the basis of the experimental steps of Example 1, the sodium sulfide aqueous solution with a concentration of 28.6 g / L was replaced by an ethanol solution of sulfur powder with a concentration of 11.75 g / L.
[0105] Fig.13 It is a schematic diagram of the ball milling time and average particle size of Example 1 of the present invention and Comparative Examples 2-5.
[0106] like Fig.13 As shown, the ball milling in the sodium sulfide aqueous solution of Example 1 has the best effect on particle size crushing, especially after the ball milling time reaches 100 minutes, the average particle size after ball milling in the sodium sulfide aqueous solution decreases significantly, the ethanol solution of sulfur powder in Comparative Example 5 has the second best effect, and the sodium thiosulfate aqueous solution and thiourea ethanol solution in Comparative Examples 3-4 have poor effects.
[0107] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for enhancing the pulverization of zero-valent iron in wet grinding, characterized in that: The crushing steps are as follows: S1, adding zero-valent iron powder to a sodium sulfide aqueous solution to form a slurry to be ground, wherein the concentration of the sodium sulfide aqueous solution is 28-29 g / L; S2, loading grinding beads into a wet ball mill, adding the slurry to be ground into the wet ball mill for grinding to obtain slurry, the grinding time is 10-640 min; S3, taking out the slurry from the wet ball mill, placing the slurry into a magnetic separation device for solid-liquid separation, collecting the ground sulfide-modified zero-valent iron particles and washing them with ethanol; as well as S4, placing the washed sulfurized modified zero-valent iron particles in a vacuum drying oven, controlling the temperature at 40-60° C. for drying until the residual moisture and ethanol are completely removed.
2. The method for enhancing the pulverization of zero-valent iron in wet grinding according to claim 1, characterized in that: in, The content of zero-valent iron in the zero-valent iron powder is higher than 98.5%, and the median particle size of the zero-valent iron particles is 3.0-3.2 microns.
3. The method for enhancing the pulverization of zero-valent iron in wet grinding according to claim 1, characterized in that: in, The grinding beads are zirconia beads with a weight of 0.7-0.8 kg and a diameter of 0.2-0.4 mm, and the input amount is 0.5 / kg L ~1 kg / L.
4. The method for enhancing the pulverization of zero-valent iron in wet grinding according to claim 1, characterized in that: in, During the grinding process, the temperature in the wet grinding machine cavity is controlled at 8-12°C.
5. The method for enhancing the pulverization of zero-valent iron in wet grinding according to claim 4, characterized in that: in, The rotation speed of the wet ball mill is 1900-2100 rpm.
6. The method for enhancing the pulverization of zero-valent iron in wet grinding according to claim 1, characterized in that: in, The grinding time is 100-640 min.
Citation Information
Patent Citations
A method for preparing composite zero-valent iron materials based on wet ball milling of soluble sulfides
CN113102761B
Method for preparing sulfurized nano zero-valent iron material based on elemental sulfur wet ball milling and application of sulfurized nano zero-valent iron material
CN116275059A
Method for preparing sulfur-nitrogen modified zero-valent iron through wet ball milling, sulfur-nitrogen modified zero-valent iron and application of sulfur-nitrogen modified zero-valent iron
CN118595433A
Preparation method of modified micron zero-valent iron and application method of modified micron zero-valent iron in remediation of heavy metal contaminated soil
CN106180735A
Preparation method for iron-ferrous sulfide composite
CN106536097A